THE THE IMPACT OF HUMAN CAPITAL ON STRATEGIC PLANNIG AND IMPLEMENTATION OF CRM FOR ENHANCING CUSTOMER REALITIONSHIP IN ENVEROUMENT AND RESOURCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In today's dynamic business landscape, effective strategic planning and the implementation of Customer Relationship Management (CRM) strategies are crucial for organizations, particularly those operating in the field of environment and resources. This article explores the significant influence of human capital on the strategic planning process and the successful deployment of CRM systems aimed at improving customer relationships within this sector. Drawing upon interdisciplinary research from management, environmental studies, and information technology, this study investigates the intricate relationship between human capital, strategic planning, and CRM implementation. Through a comprehensive review of relevant literature and case studies, the article highlights key considerations for leveraging human capital to optimize strategic planning and CRM implementation, ultimately fostering sustainable customer relationships in environment and resources.